Combined use of CA 125 and Inhibin as tumor marker for detection of ovarian cancer in comparison to CA 125 or Inhibin alone - Dubbewar, Avinash P.; Pathak, B.; Biswas, Manas; Malhotra, Gunjan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Ovarian cancers are diagnosed at an advanced stage. Early diagnosis is the key to reduce death from ovarian cancer. The present study is an effort to assess the suitability of combined test using CA 125 and Inhibin for early diagnosis of ovarian cancer as compared to CA125 or Inhibin alone. Methods: Fifty women with clinical suspicion of ovarian malignancy attending Gynae OPD were enrolled. All of these women were subjected to estimation of CA 125 and Inhibin levels prior to surgical intervention. A value of 35 IU/ml was taken as positive for CA 125. For Inhibin, 10.5 pg/ml was taken as cut off for premenopausal patients, whereas, any detectable assays were taken as positive for postmenopausal patients. The results were analyzed after establishing final histopathology of the disease. Results: Out of 50 patients recruited, 30 (60%) were found to have carcinoma ovary and 20 (40%) were found to have benign diseases. Out of 30 cases of carcinoma ovary, CA125 was raised in 81% of cases and Inhibin was raised in 78% of cases. For detection of carcinoma ovary, CA 125 was found to have a sensitivity of 90% and specificity of 60% with a positive predictive value of 77% and negative predictive value of 80% which were statistically significant. Sensitivity and specificity of serum Inhibin for the same was 86.6% and 20% respectively. The positive and negative predictive value were 61.9% and 50%, which were not statistically significant. Sensitivity and specificity of combined CA125 and Inhibin were 100% and 30% respectively. The positive and negative predictive value were 68.1% and 100% respectively, which were statistically significant. Conclusions: Combined use of CA125 and Inhibin has got better sensitivity and specificity in detection of ovarian cancer in comparison to CA 125 or Inhibin used alone.